EFEKTIVITAS KINERJA PEGAWAI KONTRAK DI KABUPATEN JEMBRANA (STUDI KASUS KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA) - Yuka, Ni Made Diah Pradnyasuari Ananda; Winaya, I Ketut; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2023)
his research is motivated by several problems with contract employees at the personnel and human resource development agency, namely work procedures that are not in accordance with educational backgrounds, work skills, lack of training for contract employees, small salaries and delays in receiving salaries, some employees who are less discipline such as coming late to the office and leaving before office hours are over. This research uses performance theory according to Bernardian & Russell (in Faustino Cardoso Gomes 2005:142). The results of the study show that the performance of contract employees at the Jembrana Regency Personnel and Human Resources Development Agency is measured to be quite good, but there needs to be an increase in performance in indicators of quality, quantity and persistence at work. Keywords: Effectiveness, Contract Employee Performance, Personnel Agency and Human Resource Development.